KARAKTERISTIK FENOTIF ISOLAT KLINIK Escherichia coli O157:H7 PADA MEDIA SORBITOL MAC CONKEY AGAR (SMAC) - Wahyu Hidayati; I Gede Rai Maya Temaja; Ni Nengah Dwi Fatmawati (Journal of Agricultural Science and Biotechnology, 2018)
Phenotypic Characteristic of Escherichia coli O157: H7 Clinical Isolates on MacConkey Agar with Sorbitol (SMAC)Escherichia coli is a Gram-negative, rod-shaped bacterium, and commonly has flagella. Most of E. coli strains are normal flora in digestive tract of human, but some serotypes are pathogen for human and animal. One of pathogenic E. coli strain that causes a severe infection in humans (hemorrhagic colitis and hemolytic uremic syndrome) is known as Enterohemorrhagic Escherichia coli (EHEC) with cattle as their natural reservoir. E. coli O157:H7 is the most important and pathogenic serotype of EHEC which responsible for outbreak of Hemorrhagic Colitis and Hemolytic Uremia Syndrome. Accurate and cheap method detection of E. coli O157:H7 is needed to help early detection diagnosis and therapy. Therefore, the aim of this study is investigate phenotypic characteristics of E. coli O157:H7 isolated from clinical specimens using MacConkey Agar with Sorbitol (SMAC) media. Three E. coli clinical isolates from Sanglah General Hospital showed colorless non-sorbitol fermenting colony in SMAC media as phenotypic characteristic of E. coli O17:H7, therefore SMAC may beused on are of confirmation methods for E. coli O157:H7 detection from clinical isolats.